Analisis Konsep Nyeri Akut pada Pasien Bedah : Tinjauan Keperawatan - Bekti Wahyuning Tias; Anistasia Aditya Suryani; ⁠Siti Aisah; Satriya Pranata; Fatkhul Mubin (Pusat riset dan Inovasi Nasional, 2026)
Acute pain is a complex phenomenon frequently experienced by post-surgical patients. If not properly managed, it can hinder the recovery process and increase the risk of chronic complications. This study aims to conduct an in-depth analysis of the concept of acute pain in surgical patients from a nursing perspective to improve the quality of care. The method used was a narrative literature review, analyzing various research articles and clinical protocols related to surgical pain management. The study findings indicate that acute post-surgical pain involves sensory and emotional dimensions influenced by the type of surgical procedure, individual pain threshold, and the effectiveness of pharmacological and non-pharmacological interventions. Furthermore, the role of nurses in conducting accurate pain assessments and patient education is a key factor in successful pain management. The implications of this study emphasize the importance of implementing integrated multimodality pain management protocols and improving nurses' competency in conducting intensive monitoring. Optimizing pain management is expected to accelerate patient mobilization, shorten hospital stays, and increase patient satisfaction with nursing services.